Electrochemical determination of antioxidant capacities in flavored waters by guanine and adenine biosensors - Kamel, Ayman H. (2013)
The immobilization and electro-oxidation of guanine and adenine asDNA bases on glassy carbon electrode are evaluated by square wave voltammetric analysis. The influence of electrochemical pretreatments, nature of supporting electrolyte, pH, accumulation time and composition of DNA nucleotides on the immobilization effect and the electrochemical mechanism are discussed. Trace levels of either guanine or adenine can be readily detected following short accumulation time with detection limits of 35 and 40 ngmL−1 for guanine and adenine, respectively. The biosensors of guanine and adenine were employed for the voltammetric detection of antioxidant capacity in flavored water samples. The method relies on monitoring the changes of the intrinsic anodic response of the surface-confined guanine and adenine species, resulting from its interaction with free radicals from Fenton-type reaction in absence and presence of antioxidant. Ascorbic acid was used as standard to evaluate antioxidant capacities of samples. Analytical data was compared with that of FRAP method.